Depressive symptoms and inflammation are independent risk factors of fatigue in breast cancer survivors. Issue 10 (14th February 2017) - Xiao, C.; Miller, A. H.; Felger, J.; Mister, D.; Liu, T.; Torres, M. A.
Abstract : Background: Psychosocial and inflammatory factors have been associated with fatigue in breast cancer survivors. Nevertheless, the relative contribution and/or interaction of these factors with cancer-related fatigue have not been well documented. Method: This cross-sectional study enrolled 111 stage 0–III breast cancer patients treated with breast surgery followed by whole breast radiotherapy. Fatigue was measured by the total score of the Multidimensional Fatigue Inventory-20. Potential risk factors included inflammatory markers (plasma cytokines and their receptors and C-reactive protein; CRP), depressive symptoms (as assessed by the Inventory of Depressive Symptomatology–Self Reported), sleep (as assessed by the Pittsburgh Sleep Quality Index) and perceived stress (as assessed by the Perceived Stress Scale) as well as age, race, marital status, smoking history, menopause status, endocrine treatment, chemotherapy and cancer stage. Linear regression modeling was employed to examine risk factors of fatigue. Only risk factors with a significance level <0.10 were included in the initial regression model. A post-hoc mediation model using PROCESS SPSS was conducted to examine the association among depressive symptoms, sleep problems, stress, inflammation and fatigue. Results: At 1 year post-radiotherapy, depressive symptoms ( p <0.0001) and inflammatory markers (CRP: p = 0.015; interleukin-1 receptor antagonist: p = 0.014; soluble tumor necrosis factor receptor-2: p = 0.009 in separate models) were independent risk factors of fatigue. Mediation analysis showed that depressive symptoms also mediated the associations of fatigue with sleep and stress. Conclusions: Depressive symptoms and inflammation were independent risk factors for cancer-related fatigue at 1 year post-radiotherapy, and thus represent independent treatment targets for this debilitating symptom.